2022
DOI: 10.1002/acn3.51559
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of melatonin in term neonatal models of perinatal hypoxia‐ischaemia

Abstract: Objective: Neonatal encephalopathy (NE) is an important cause of mortality and disability worldwide. Therapeutic hypothermia (HT) is an effective therapy, however not all babies benefit. Novel agents are urgently needed to improve outcomes. Melatonin in preclinical studies has promising neuroprotective properties. This meta-analysis assessed the efficacy of melatonin in term animal models of NE on cerebral infarct size, neurobehavioural tests and cell death. Methods: A literature search was carried out using E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 59 publications
0
16
0
Order By: Relevance
“…A meta-analysis showed the neuroprotective effects of melatonin in experimental models of hypoxic-ischemic encephalopathy by reducing neuronal death and improving neurobehavioral and neurological outcomes ( Figure 1 ) [ 133 ]. In addition, animal studies have indicated that melatonin may ameliorate Alzheimer’s disease-related alterations in amyloid, tau protein and neurotransmission ( Figure 1 ).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…A meta-analysis showed the neuroprotective effects of melatonin in experimental models of hypoxic-ischemic encephalopathy by reducing neuronal death and improving neurobehavioral and neurological outcomes ( Figure 1 ) [ 133 ]. In addition, animal studies have indicated that melatonin may ameliorate Alzheimer’s disease-related alterations in amyloid, tau protein and neurotransmission ( Figure 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…The neuroprotective effects of melatonin have been present in single therapy as well as in combination with hypothermia [ 133 ]. The analysis of the studied subgroups showed greater effectiveness after the administration of melatonin before or immediately after the injury and with ethanol auxiliaries [ 133 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations